Ideologia e Poder Judiciário: um processo histórico de construção de valores - Linardi, Rafael da Cruz Gouveia (2017)
This dissertation examines law from an essentially cultural perspective, that is, as a phenomenon arising from the gradual construction of values in the course of history. Among the sources of law, the study focuses on the so-called judicial source, that is, the right that arises from decisions handed down by judges and courts. It seeks to comprehend the ideologies that serve as a framework for decisions made by judges, within the contemporary panorama. It is assumed that the judicial activity is predominantly interpretative, requires a position, and, consequently, a choice of values. As a starting point, the study shows opinion poll results in which judges were able to voice their considerations on the most relevant aspects. It also reveals that, in general, judges take into consideration in their decisions both the paradigm of legality and concomitantly the social consequences that their sentences may lead to. Considering those paradigms as simultaneously embedded, the study analyzes in greater depth, the foundations of both stances: on one hand the "legalist" and on the other the "social" one. Through a historical approach, it identifies that "legalism" is the result of constant and permanent search of the human being for security and stability. Moreover, it reveals that legalism can also relate to an "ideological legal positivism" Otherwise, the concern with "social consequences of judicial decisions" gains ground, at a time when the rapprochement of law with ethics is sought. Besides, judicial positions strengthen elements of the Marxist critique, unleashing the so-called "judicial activism”. Finally, the study examines recent jurisprudential cases in which it is possible to confirm this ideological dichotomy that is present in the intricacies of the Judicial Power